An analysis of Particularized Iplicature in to All the Boys I Loved Always and Forever: Pragmatics Approach - Valeryan Salsabilla Maurarochelle; Ambalegin (e-Journal of Linguistics, 2023)
The aimed of this research is to examine the part of the particularizedconversational implicature and flouting of maxim found in a Netflix movie,named To All the Boys I Loved : Always and Forever. The researcher usedthe particularized conversational implicature theory by Yule (1996) toidentify the utterances and the flouting of maxim by Grice (1976) tocategorize the type. The design of this research is descriptive qualitativeresearch. The researcher used the interview method by Sudaryanto to collectdata, the pragmatic identity method by Sudaryanto to analyze the data, andused the informal method by Sudaryanto to present the research result. Theresearcher collected twenty one data that contain particularizedconversational implicature, and eight of the data categorized as flouting ofmaxim quality, four data categorized as flouting of maxim quantity, five datacategorized as flouting of maxim relevant and four data categorized asflouting of maxim manner.The result concludes that out of the twenty oneanalyzed data, flouting of the maxim relevant in the particularizedconversational implicature is the most used apply in the movie.